Adaptive Packet-Level Interleaved FEC for Wireless Priority-Encoded Video Streaming. (9th August 2009) - Razavi, Rouzbeh; Fleury, Martin; Ghanbari, Mohammed
Abstract : Packet-level Forward Error Control (FEC) for video streaming over a wireless network has received comparatively limited investigation, because of the delay introduced by the need to assemble a group of packets. However, packet-level interleaving when combined with FEC presents a remedy to time-correlated error bursts, though it can further increase delay if this issue is not addressed. This paper proposes adapting the overall degree of interleaved packet-level FEC according to the display deadlines of packets, transmit buffer occupation, and estimated video input to the wireless channel, all of which address the issue of delay. To guard against estimation error, the scheme applies a conservative adaptation policy, which accounts for picture type importance to ensure that display deadlines are met, thus avoiding this defect of interleaving. The paper additionally introduces a greedy algorithm that effectively groups packet-level FEC protection according to packet priority. Priority encoding adds extra protection during deep fades. As feedback is not required, the interleaving scheme is suitable for all forms of video broadcast. A Bluetooth piconet demonstrates the packet-level FEC interleaving scheme, which provides higher quality delivered video compared to the industry-standard Pro-MPEG Cop#3r2 interleaving scheme.